Optical properties of Mg doped LiNbO3 thin films grown by polymeric precursor method - Simões, A. Z. [UNESP]; Gonzalez, A. H.M. [UNESP]; Cilense, M. [UNESP]; Zaghete, M. A. [UNESP]; Moura, F. [UNESP]; Ries, A. [UNESP]; Varela, J. A. [UNESP]; Stojanovic, B. D. (My University, 2004)
Polymeric precursor solution was used to deposit by spin-coating pure and Mg doped LiNbO3 thin films on sapphire substrates. The effects of magnesium addition on crystallinity, morphology and optical properties of the annealed films were investigated. X-ray diffraction patterns indicate the oriented growth of the films. AFM studies show that the films are very homogeneous, dense and present smooth surfaces. The refractive index and optical losses obtained by the prism coupling method were influenced by the magnesium addition.